Assessment of Clinical and Radiological Results After Anterior Cervical Discectomy and Fusion - Özden, Mahmut (Cerrahpaşa Medical Journal, 2023)
Objective: Anterior cervical discectomy and fusion (is one of the important options for the treatment of cervical disc herniation. The aim of this study was to examine the effects of anterior cervical discectomy and fusion on coronal balance, apart from the reduction in pain intensity, angle difference, and sagittal balance, which has been frequently studied before. Methods: Clinical and radiological follow-up results after anterior cervical discectomy and fusion procedure were evaluated in 41 patients. Standard anterior cervical microdiscectomy, osteophytectomy, and root decompression were performed by the same neurosurgeon. The pre- and postopera- tive sagittal balances of the patients, the effect of the angulation difference that will be created by the cage and the pain scores (visual analog scale) were determined. C1-C2 angle, C2-C7 lordosis angle, and T1 slope angle were measured on the lateral radiograph of the patients. Number Cruncher Statistical System program was used for statistical analysis. Results: The lordotic increases in the postoperative C1-C2 and C2-C7 angles of the cases compared to the preoperative period were statistically sig- nificant (P = .001 and P = .004, respectively). The changes in the T1 slope angles and in the postoperative coronal balance measurements after the operation compared to the preoperative period were not significant (P = .232 and P = .753, respectively). The decrease in the postoperative visual analog scale scores of the cases compared to the preoperation was significant (P = .001). Conclusion: While no significant change was found in the T1 slope angle for lordosis after surgery, significant increases in the C1-C2 and C2-C7 lordosis angles were accompanied by a significant decrease in pain. Cite this article as: Özden M. Assessment of clinical and radiological results after anterior cervical discectomy and fusion. Cerrahpaşa Med J. 2023;47(2):171-175.